Analisis Faktor Penolakan Warga Negara Indonesia Eks ISIS ke Indonesia - Adha , Fajri; Yumitro, Gonda (Pusat Kajian Keamanan Nasional (Puskamnas) Universitas Bhayangkara Jakarta Raya, 2022)
This article aims to analyze several factors that caused the government to reject the return of ex-ISIS Indonesian citizens to Indonesia. This research was explanatory research using a qualitative approach. Meanwhile, the data collection technique was a literature study using the Google Scholar search engine and Harzing Publish or Perish. The authors used Miles and Huberman’s data analysis technique using the interactive model qualitative data analysis technique. The authors found that two factors influenced the rejection of the return of ex-ISIS Indonesian citizens: internal and external factors. Internal factors consist of political factors, security factors, and cultural factors. Meanwhile, the external factors related to the Global War on Terrorism (GWOT). As for the political factor, the ex-ISIS members have a radical ideology for gaining their political interests. Then from the security factor, it was found that the ex-ISIS members had combat skills and knowledge, which would significantly affect the security and living conditions of the community. Finally, from cultural factors, ex-ISIS members tend to have an intolerant nature resulting from their ideology. The existence of this intolerant nature will undoubtedly clash with the diverse cultural conditions of the Indonesian people. The external factor is Indonesia’s participation in the effort to fight global terrorism together with other countries.